EP765 The effect of malformina1 on cisplatin-sensitive and cisplatin-resistant ovarian cancer cell lines. (1st November 2019) - Abdullah, N; Al Balushi, N; Al-Bahlani, S; Dobretsov, S; Hassan, I; Sang, T; Tamimi, Y; Burney, I
Abstract : Introduction/Background: High grade epithelial ovarian cancer is often associated with drug resistance and poor outcomes. Previously, we demonstrated significant cytotoxic efficacy of a marine compound MalforminA1 against MCF-7 breast cancer cell line. Methodology: We tested the anti-cancer potential of MalforminA1on cisplatin-sensitive (A2780s) and cisplatin-resistant (A2780cp) ovarian cancer cell lines using AlamarBlue assay, flow cytometry, western blot and RT-qPCR. Results: MalforminA1 had significantly higher cytotoxic activity when compared to cisplatin in both A2780s and A2780cp cell lines (IC50 0.23µMand 0.34µM compared to 31.4 µM and 76.9 µM p<0.001respectively).The cytotoxic effect of MalforminA1 was confirmed using flow cytometry where 66% of A2780s and 44% of A2780cp cells underwent apoptosis after48 hours of treatment. Also, morphological changes were seen in the cells upon the exposing to MalforminA1for 24h. To investigate the mechanism of apoptosis induction by malforminA1, we examined the expression of bcl2, p53, caspase3 and caspase9 at the RNA and proteins levels using RT-qPCR and western blot respectively. A significant reduction in m-RNA and protein levels was seen in both bcl2 and p53 in the treated cell lines compared to the non-treated cells(p<0.001). Similar results were obtained with anti-apoptotic proteins bcl-x and bcl-xl using western blot (p<0.01). On the other hand, caspases 3/9protein levels were not affected by MalforminA1treatment, suggesting that MalforminA1induces apoptosis by affecting bcl2 signaling pathway. Conclusion: MalforminA1 showed promising anti-cancer activity by introducing apoptosis, and therefore warrants further investigation. Disclosure: We are greatly thankful for the support through His Majesty Trust Fund Grant (SR/MED/MEDE/17/01).